2017
DOI: 10.1111/jth.13618
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical characterization of the prothrombin Belgrade mutation in a large Serbian pedigree: new insights into the antithrombin resistance mechanism

Abstract: Background The recently reported c.1787G>A mutation in the prothrombin gene leads to Arg596Gln replacement in the protein molecule (prothrombin Belgrade). This substitution impairs binding of antithrombin to thrombin and results in inherited thrombophilia, known as antithrombin resistance. Objectives We aimed to elucidate the clinical and biochemical characteristics of thrombophilia associated with antithrombin resistance in a large Serbian family with the prothrombin Belgrade mutation. Patients and methods Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 19 publications
5
22
1
Order By: Relevance
“…All VTE-causing prothrombin mutations including Arg596Gln, Arg596Trp and Arg596Leu were reported to decrease prothrombin clotting activity. We found that deceased prothrombin activity was a simple and valuable test for screening Arg596 associated mutation as previously mentioned,12 and decreased prothrombin activity warrants further genetic analysis of the F2 gene.…”
Section: Discussionsupporting
confidence: 75%
“…All VTE-causing prothrombin mutations including Arg596Gln, Arg596Trp and Arg596Leu were reported to decrease prothrombin clotting activity. We found that deceased prothrombin activity was a simple and valuable test for screening Arg596 associated mutation as previously mentioned,12 and decreased prothrombin activity warrants further genetic analysis of the F2 gene.…”
Section: Discussionsupporting
confidence: 75%
“…The thrombotic clinical penetrance of antithrombin‐resistant prothrombinemia is estimated to be equivalent or higher than that of antithrombin deficiency. With respect to prothrombin Belgrade (Arg596Gln), 60% heterozygous carriers of this mutation in the reported family developed venous thrombosis during their lifetime, and the annual incidence rate of the first thrombosis from birth was 2.2% . Conversely, the prevalence of an antithrombin‐resistant prothrombin carrier with this mutation has not been precisely estimated among patients with VTE.…”
Section: Discussionmentioning
confidence: 97%
“…Antithrombin‐resistant prothrombin is a mutant presenting paradoxical features in thrombosis and haemostasis in vivo, that is the mutant thrombin derived from antithrombin‐resistant prothrombin displays a mild decline in the procoagulant activity. However, a substantial impairment in its inactivation by antithrombin results in a prolongation of the procoagulant activity, causing thromboembolism in some patients . In clinical laboratory tests, plasma from the patient with a heterozygous ATR mutation does not exhibit a significant alteration in PT and APTT levels .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations